2018
DOI: 10.1111/jth.14006
|View full text |Cite
|
Sign up to set email alerts
|

Platelets loaded with liposome‐encapsulated thrombin have increased coagulability

Abstract: Background Platelets are integral to clot formation and are often transfused to stop or prevent bleeding. However, transfusions of platelets are not always effective, particularly in the most severe cases of hemorrhage. Nanoparticle systems have been developed to mimic platelets but inherently lack important aspects of platelet function, which limits their potential effectiveness. Objectives Increasing the natural coagulability of transfusable platelets could increase their efficacy during treatment of severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Plasma proteins can bind to LNPs, which affects their ability to be internalized by cells 22 . While the effect of incubating platelets in buffer before reconstituting in plasma was not fully characterized in this paper, we have previously shown that platelets prepared with protein-loaded LNPs can still clot blood in vitro after short periods of storage in buffer 27 . Here, the icLNPs did not activate the platelets or affect their ability to aggregate or spread.…”
Section: Discussionmentioning
confidence: 96%
“…Plasma proteins can bind to LNPs, which affects their ability to be internalized by cells 22 . While the effect of incubating platelets in buffer before reconstituting in plasma was not fully characterized in this paper, we have previously shown that platelets prepared with protein-loaded LNPs can still clot blood in vitro after short periods of storage in buffer 27 . Here, the icLNPs did not activate the platelets or affect their ability to aggregate or spread.…”
Section: Discussionmentioning
confidence: 96%
“…Incorporating thrombin-containing liposomes into platelets prior to transfusion can increase their thrombogenicity likely by platelet incorporation of thrombin and subsequent release upon activation at an injury site. 57 Platelet-derived microparticles (PMPs) have shown possible therapeutic benefit in promoting hemostasis. These microparticles of platelet cell membrane are procoagulant, 58,59 and their levels in circulation increase after injury.…”
Section: Novel Therapeutic Approaches To Platelet Dysfunctionmentioning
confidence: 99%
“…However, another study showed that the platelet-derived hemostatic agent could neither reduce ear bleeding time nor improve clot strength in a rabbit thrombocytopenic model [117]. The limited efficacy, immunogenicity and risk of pathogen infection prompt the development of new intravenous hemostats, including synthetic platelets and polymers [46,49], and platelets loaded with liposomeencapsulated thrombin [118].…”
Section: Dried Plateletsmentioning
confidence: 99%